Izoencimi aldo/keto-reduktaz iz poddružine 1C kot tarče za razvoj zdravilnih učinkovin - Brožič, Petra (Farmacevtski vestnik, 2009)
Aldo-keto reductases catalyze reduction of carbonyl containing substrates to alcohols. Four human hydroxysteroid-dehydrogenases, members of the AKR1 C subfamily (AKR1 C1-AKR1 C4), are involved in biosynthesis and inactivation of steroid hormones, and metabolism of other steroids, prostaglandins and xenobiotics. Since AKR1 C enzymes have broad spectrum of physiological roles they represent interesting drug targets for treatment of different pathophysiological conditions like hormone-de pen dent cancers, acute myeloid leukaemia, lung cancer, oral cancer and non-Hodgkin Iymphoma. These enzymes also affect distribution of fat tissue in obesity. Over the last decade, the number of publications on correlation between AKR1C expression and different pathophysiological conditions has increased enormously suggesting that inhibition of these enzymes would be beneficial for treatment of these diseases. Inhibitors of these tissue specific enzymes could represent anovel class of drugs, the so called selective intracrine modulators.
Keywords: encimi; ksenobiotiki; prostaglandini; reduktaze; steroidi